2014
DOI: 10.3892/ol.2014.1839
|View full text |Cite
|
Sign up to set email alerts
|

A furin inhibitor downregulates osteosarcoma cell migration by downregulating the expression levels of MT1-MMP via the Wnt signaling pathway

Abstract: This study aimed to explore the exact mechanism of the effect of a furin inhibitor on the migration and invasion of MG-63 and Saos-2 osteosarcoma cells. MG-63 and Saos-2 osteosarcoma cells were treated with regular culture medium in the presence or absence of 480 nM α1-antitrypsin Portland (α1-PDX). Wound-healing and Transwell assays were used for the detection of the effects of α1-PDX on MG-63 and Saos-2 osteosarcoma cell migration and invasion. Western blot analysis and reverse transcription-polymerase chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 37 publications
3
12
0
Order By: Relevance
“…The results showed inhibition of PIM1 expression by PIM1 siRNA was accompanied with down‐regulation of Bcl‐2, survivin, and Bcl‐XL expressions and change in Bcl‐2 was the most significant. MT1‐MMP is a zinc‐dependent type‐I transmembrane metalloproteinase that plays pivotal roles in cellular migration and invasive processes in osteosarcoma . In this study, the decreased PIM1 expression by siRNA was also accompanied by down‐regulated expression of MT1‐MMP.…”
Section: Discussionmentioning
confidence: 61%
“…The results showed inhibition of PIM1 expression by PIM1 siRNA was accompanied with down‐regulation of Bcl‐2, survivin, and Bcl‐XL expressions and change in Bcl‐2 was the most significant. MT1‐MMP is a zinc‐dependent type‐I transmembrane metalloproteinase that plays pivotal roles in cellular migration and invasive processes in osteosarcoma . In this study, the decreased PIM1 expression by siRNA was also accompanied by down‐regulated expression of MT1‐MMP.…”
Section: Discussionmentioning
confidence: 61%
“…Additionally, the Wnt/b-catenin signaling is correlated with MMP-1 and MMP-7 levels in other tumor cells. 34,35 We demonstrated that Wnt/b-catenin pathway was activated in glioma cells, but inactivated by GPNMB suppression, and the activity of MMPs in glioma cells was mediated by Wnt/bcatenin pathway.…”
Section: Discussionmentioning
confidence: 96%
“…The associations between different signaling pathways and MMPs have been investigated in a number of cell culture systems (4648). Using selective pharmaceutical inhibitors of EGFR downstream signaling pathway effectors, the present study revealed that MMP-1 expression was upregulated through the MAPK/ERK signaling pathway in SiHa cells treated with EGF and MβCD, and that the PI3-K/AKT, p38 MAPK and JNK/MAPK signaling pathways were not involved in this process.…”
Section: Discussionmentioning
confidence: 99%